Habitat of Banggai Cardinalfish (Pterapogon kauderni) Spread Across the Coast of Kayumalue Village, Palu Bay, Central Sulawesi - Rasul, Rasul; Lahati, Sonny; Ndobe, Samliok; Sababuli, Jeklin M (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The Banggai cardinalfish (Pterapogon kauderni Koumans, 1933) is an endemic species that inhabits a limited habitat in shallow waters. This species is a widely traded marine ornamental fish. However, since late 2007, the International Union for Conservation of Nature (IUCN) has classified P. kauderni as an endangered species. Changes in P. kauderni habitat in Palu Bay have been reported, particularly in the waters of Mamboro Village Beach. According to local community information, this species has been introduced to Kayumalue Pajeko Village Beach, also within the Palu Bay area. Daily human activities and environmental changes caused by natural disasters and post-tsunami recovery necessitate annual updates on population development data and habitat conditions. This study aimed to reassess the habitat conditions of P. kauderni in the waters of Kayumalue Village, Palu Bay. Observation results showed that P. kauderni was only found in the macrohabitat of sea urchins. Meanwhile, along the observed transect, no recruit-sized P. kauderni were found. This is suspected to be due to the limited availability of macro habitat types such as anemones or other soft corals.